Exploring Phytoremediation Potential Of Alternanthera Phyloxeroides (Mart.) Griseb.: A Case Study Using Grey Water Generated In The Miranda House Campus (International Journal of Environmental Sciences, 2025)
Environmental pollution, including water pollution, is one of the major challenges facing the world today. With fresh water supplies being under strain in many cities and countries around the world, water recycling becomes the only way forward. Bioremediation and especially phytoremediation is an environment friendly solution. This paper explores the phytoremediation potential of Alternanthera philoxeroides in terms of some common water quality parameters like pH, TDS, electrical conductivity, salinity, sulphate, phosphate, chloride and dissolved oxygen (DO). Alternanthera philoxeroides show promising results, with water quality improvement for investigated parameters in laundry water. There was a significant increase in DO levels and decrease in TDS and chlorides in waste water. The results imply that Alternanthera philoxeroides may be a useful agent for improving water quality, offering a sustainable and economical method of treating waste water.